Design an Automatic Condenser in Swallow Bird House - Asrul, Andi Aliem Adrian; Syafaat, Achamdi; Baktiar, Baktiar; Usman, Usman (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2024)
This design is a system development carried out by swallow breeders in stabilizing the temperature and humidity of swallow houses. This design uses the principles of the Internet of Things (IoT), which will monitor temperature and humidity through internet media. This design aims to make a temperature and humidity control system in the swallow house automatically and find out the level of accuracy of temperature and humidity readings in the design made. This design uses a Wemos D1 Mini Board microcontroller that controls components such as DHT22 sensors, DS18B20 sensors and relays. The result of this design can control the condenser automatically, when the temperature and humidity are above the standard temperature, it will turn on the condenser automatically.